Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1136/bjsports-2013-092558.18
|View full text |Cite
|
Sign up to set email alerts
|

Can We Test Swimming Lessons Skills in Drowning Prevention?

Abstract: Background Drowning is the third leading cause of death worldwide (WHO, 2010). According to Brenner et al (2009) participating in swimming lessons (SL) can reduce by 88% the risk of drowning in children 1–4 years old, despite some controversy regarding the most appropriate swimming programs (Ward, 2009). On the other hand no studies tested the skills acquired in SL in drowning prevention. So we proposed a test to evaluate the survivability of a child that accidentally falls into the water. Methods Twenty two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…These are skills that demand higher motor coordination in synchronizing balance, breathing, arms, and legs actions, which may require to reach a higher motor development stage, to take in the most effective and efficient swimming pattern. Nevertheless, Asher et al [ 51 ] with toddlers and Oliveira et al [ 52 ] with five-year-old children, reported the ability of children to roll over and turn. Moreover, those skills are included further in swimming programs and may require more aquatic experience to be well perceived and mastered.…”
Section: Discussionmentioning
confidence: 99%
“…These are skills that demand higher motor coordination in synchronizing balance, breathing, arms, and legs actions, which may require to reach a higher motor development stage, to take in the most effective and efficient swimming pattern. Nevertheless, Asher et al [ 51 ] with toddlers and Oliveira et al [ 52 ] with five-year-old children, reported the ability of children to roll over and turn. Moreover, those skills are included further in swimming programs and may require more aquatic experience to be well perceived and mastered.…”
Section: Discussionmentioning
confidence: 99%
“…The manner of the entry and its consequences influence the surfacing process and its success or failure (Junge, Blixt, & Stallman, 2010). Breath holding and buoyancy control (among other competencies) are challenged while regaining the surface (Oliveira, Aranha, Resende, Cardoso, Pimenta, & Garrido, 2013). Surfacing in itself is a specific skill and includes the above, plus some form of propulsion to the surface.…”
Section: Resultsmentioning
confidence: 99%
“…They then needed to roll over to their back for ease of breathing and to turn towards the point of entry. A study of 5-year-old children (N = 22) showed that the random positions the children found themselves in after falling from a boat demanded that they needed to be able to both roll and turn (Oliveira et al, 2013). Both rolling over and turning were negatively influenced by clothing (Laakso, Horneman, Grimstad, & Stallman, 2014).…”
Section: B Turn Left and Right On Front And Backmentioning
confidence: 99%
“…The dramatic decline in drowning rates in many countries has been attributed, inter alia, to improved swimming training (Austin & Macintosh, ; Brenner, Saluja, & Smith, ; Kao et al, ). Given that two key factors contributing to drowning in infants are children not having: (a) suitable swimming lessons and (b) experience of playing near or in water regularly (Yang, Nong, Li, Feng, & Lo, ), learn‐to‐swim classes can potentially significantly reduce child drownings (Asher, Rivara, Vance, & Dunne, ; Brenner et al, ; Ekchaloemkiet & Gerdmongkolgan, ; Moreno, ; Nguyen, Pham, & Linnan, ; Oliveira et al, ; Wallis et al, ).…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%